Developing high performance RF heating scenarios on the WEST tokamak. (1st December 2022) - Goniche, M.; Ostuni, V.; Bourdelle, C.; Maget, P.; Artaud, J.F.; Bernard, J.M.; Bobkov, V.; Bucalossi, J.; Clairet, F.; Colas, L.; Desgranges, C.; Delpech, L.; et al.
Abstract: High power experiments, up to 9.2 MW with LHCD and ICRH, have been carried out in the full tungsten tokamak WEST. Quasi non inductive discharges have been achieved allowing to extend the plasma duration to 53 s with stationary conditions in particular with respect to tungsten contamination. Transitions to H mode are observed, and H-modes lasting up to 4 s have been obtained. The increase in stored energy is weak since the power crossing the separatrix is close to the L–H threshold. Hot L mode plasmas (central temperature exceeding 3 keV) with a confinement time following the ITER L96 scaling law are routinely obtained. The weak aspect ratio dependence of this scaling law is confirmed. Tungsten accumulation is generally not an operational issue on WEST. Difficulty of burning through tungsten can prevent the discharge from accessing to a hot core plasma in the ramp-up phase, or can lead to rapid collapse of the central temperature when radiation is enhanced by a slight decrease of the temperature. Except a few pulses post-boronization, the plasma radiation is rather high ( P rad/ P tot ∼ 50%) and is dominated by tungsten. This fraction does not vary as the RF power is ramped up and is quite similar in ICRH and/or LHCD heated plasmas. An estimate of the contribution of the RF antennas to the plasma contamination in tungsten is given.